Value of patology of the vestibular analyzer in pathogenesis impellent frustration in children with cerebral paralyses - B. M. Glukhov (Бюллетень сибирской медицины, 2009)
Value of functions of the vestibular analyzer of the child in formation of its motility is shown. 11 patients aged till three years, suffering by a childrens cerebral paralysis, have been surveyed. Was studied the group of the tonic reflexes in dynamics, afferent arch of which was the vestibular mechanism and its conductors. Infringement of degree of expressiveness of tonic reflexes and their late reduction are a principal cause of formation of a pathological impellent stereotype at the child.